Determining the Evaluation of Daylight Parameters on the Basis Simulation Model for the Tropical Climate - Dabe, Trupti J. (Current Approaches in Science and Technology Research Vol. 12, 2021)
Use of natural daylight in the building is energy saving with respect to illumination levels and health benefits. However in, the hot and dry climatic zone increase in daylight availability may result into thermal ingress. This might lead to excess energy conservation. The aim of this paper is to evolve the methodology which could be used as a pre design tool for assessing the lighting provisions and thermal performance of spaces within buildings adopted by designers during the design process. The field measurements were conducted on the liveable spaces of a dwelling unit of the Nagpur region. Simulation studies using Ecotect Analysis 2011 was conducted for both illumination and thermal energy. The field measurements were compared with the simulated results. It has been found that the percentage difference (PD) between the Ecotect measurements (EM) and field measurements (FM) for both thermal loads and an illuminance level was less than 15%, the simulated model was considered precise for further study. The result imply that the simulated model would be ample for designers to evaluate the parameters associated to wall to window ratio, shading devices with respect to orientation of the building which helps to achieve the optimum useful daylight index.